Developing competencies in public health: a scoping review of the literature on developing competency frameworks and student and workforce development - Melissa MacKay; Caitlin Ford; Lauren E. Grant; Andrew Papadopoulos; Jennifer E. McWhirter (Frontiers in Public Health, 2024)
Effective and precise public health practice relies on a skilled and interdisciplinary workforce equipped with integrated knowledge, values, skills, and behaviors as defined by competency frameworks. Competency frameworks inform academic and professional development training, support performance evaluation, and identify professional development needs. The aim of this research was to systematically identify and examine trends in the extent, nature, and range of the literature related to developing competencies in public health. This includes developing public health competency frameworks, and how competencies are developed and maintained in students and practitioners. We used a scoping review methodology to systematically identify and report on trends in the literature. Two independent reviewers conducted title and abstract and full-text screening to assess the literature for relevance. Articles were included if they were original primary research or gray literature and published in English. No date or geographic restrictions were applied. Articles were included if they focused on developing competency statements or frameworks for public health and/or training public health students or practitioners to develop competencies. The review encompassed a range of methods and target populations, with an emphasis on building competencies through student and professional development. Foundational competency development was a primary focus, and we found a gap in discipline-specific competency research, especially within developing discipline-specific competency statements and frameworks. Several evidence-based practices for competency development were highlighted, including the importance of governance and resources to oversee competency framework development and implementation, and workforce planning. Experiential learning and competency-based training were commonly identified as best practices for building competencies. A comprehensive understanding of public health competency development—through developing and incorporating foundational and discipline-specific competencies, mapping student and practitioner training to competency frameworks, and incorporating best practices—will enable public health to create skills and an adaptable workforce capable of addressing complex public health issues.